The Effect of Work Environment and Organizational Culture through Job Satisfaction on Work Effectiveness of Lecturers of Universitas Abdurachman Saleh Situbondo - Surji Mendi; Diana Sulianti K Tobing; Dewi Prihatini (Budapest International Research and Critics University, 2022)
This study aims to examine and analyze the direct and indirect effects of the work environment and organizational culture through job satisfaction on the work effectiveness of lecturers at UNIVERSITAS ABDURACHMAN SALEH SITUBONDO. This research was conducted on permanent lecturers who are still active at Abdurachman Saleh University, Situbondo. The number of respondents in this study were 89 people. The sampling technique used is a saturated sample in which the entire population in the study is sampled. Data analysis was performed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that (1) the work environment and organizational culture had a significant positive effect on job satisfaction.